The Meanings of Representation and Political Inclusion in the Conferences of Public Policies in Brazil - Martelli, Carla Giani; Almeida, Carla; Lüchmann, Lígia (Associação Brasileira de Ciência Política, 2019)
Participatory Budgets, Public Policy Conferences and Public Policy Management Councils, among other participatory institutions in Brazil, are altering the configuration of processes that define and elaborate public policies, while incorporating citizens and civil associations into political spaces where different mechanisms of participation and representation converge. These new institutions call for reflections concerning political inclusion and representation that go beyond electoral models. We propose to contribute to these debates by discussing the perceptions of some actors, in particular the leaders of civil society organizations, with regard to conferences' capacity for inclusion, and the meanings that they attribute to representation through conferences. The research findings allow us to identify a broadening of the idea of political inclusion and to highlight some of the tensions raised by demands for representation as presence in conference spaces.
Keywords: Political Representation; Political Inclusion; Participatory Institutions; Conferences